2014
DOI: 10.4161/hv.28482
|View full text |Cite
|
Sign up to set email alerts
|

Malaria vaccine

Abstract: Malaria has long been recognized as a public health problem. At the community level, vector control, and antimalarial medicines are the main means for reducing incidence, morbidity, and mortality of malaria. A vaccine not only would bring streamlining in the prevention of morbidity and mortality from malaria but also would be more accessible if integrated with Expanded Programme of Immunization (EPI). Globally, an estimated 3.4 billion people are at risk of malaria. Most cases (80%) and deaths (90%) occurred i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
3
0
1
Order By: Relevance
“…Early success with RTS,S led to reduced priority for, and less funding being directed at vaccines targeting blood-stage malaria, delaying vaccine development for infection by parasites at this stage. However, once RTS,S was found to have poor immunogenicity in women and children and increased pediatric morbidity, research interest in blood-stage malaria vaccines significantly intensified [ 30 , 113 , 114 ].…”
Section: Recent Clinical Trials Challenges and Prospectsmentioning
confidence: 99%
“…Early success with RTS,S led to reduced priority for, and less funding being directed at vaccines targeting blood-stage malaria, delaying vaccine development for infection by parasites at this stage. However, once RTS,S was found to have poor immunogenicity in women and children and increased pediatric morbidity, research interest in blood-stage malaria vaccines significantly intensified [ 30 , 113 , 114 ].…”
Section: Recent Clinical Trials Challenges and Prospectsmentioning
confidence: 99%
“…Son yıllarda yoğun aşı çalışmaları olmasına karşın henüz klinik kullanıma girebilmiş etkili bir aşı bulunmamaktadır. Ancak yeni teknoloji ürünleri olan DNA bazlı aşıların faz çalışmaları gelecek için umut vermektedir (26,27).…”
Section: İrdelemeunclassified
“…However, there are several reasons to reevaluate the use of radiated inactivation and attenuation for the production of vaccines [ 20 21 ]. The recent successful development of irradiated vaccines for human malaria and influenza have demonstrated the feasibility and practicality of this technique, and have shown that technical problems can be overcome using existing expertise, without needing to resort to sophisticated technology [ 22 23 ]. Moreover, this technology has been used to produce an anti-cancer vaccine by inactivating cancer cells [ 24 25 26 ].…”
Section: Radiation and Vaccinesmentioning
confidence: 99%
“…Of these, P. falciparum is responsible for 92% of deaths that mostly occur in children living in sub-Saharan Africa [ 125 ]. In 2012 there was an estimated 220 million clinical cases and 0.63 million deaths worldwide from malaria infection [ 23 ]. An effective vaccine for P. falciparum is needed for use in malaria-endemic populations, but no licensed malaria vaccines and candidates have consistently produced a protective level of efficacy [ 126 ].…”
Section: Irradiated Malaria Vaccinesmentioning
confidence: 99%